The effects of fatigue on plantar pressure and balance in adolescent volleyball players with and without history of unilateral ankle injury - Farzami, A.; Anbarian, M. (Science & Sports, 2020)
The purpose of this study was to assess plantar pressure and static balance alterations after jumping and landing. According to the importance of devastating impact of improper distribution of plantar forces on the incidence of abnormal movements and stresses in the foot structure of volleyball players, studying the effect of fatigue on plantar pressure and static balance can lead to significant achievements in the evaluation of this organ's performance. In this study, 12 male adolescent volleyball players with a history of unilateral ankle injury and 12 male adolescent volleyball players without a history of unilateral ankle injury was participated. Plantar pressure characteristics and static balance in volleyball players with and without history of unilateral ankle injury was recorded before and after a fatigue from consecutive jumping and landing protocol while standing static on foot pressure. maximum pressure, mean pressure, pressure distribution, surface and romberg open and close eyes balance registered. There was a significant difference between the maximum and the mean plantar pressure and the contact surface of the right foot before and after fatigue and significant difference between the mean pressure and the pressure distribution of the healthy foot and the injured leg in individuals with a history of ankle injury also fatigue cause reduce balance in adolescent volleyball players without history of unilateral ankle injury in open eyes mode and reduce balance in adolescent volleyball players with history of unilateral ankle injury in open and closed eyes. These changes could lead to lower limb injuries.